Pectin degradation accounts for apple tissue fragmentation during thermomechanical-mediated puree production. (November 2021) - Buergy, Alexandra; Rolland-Sabaté, Agnès; Leca, Alexandre; Falourd, Xavier; Foucat, Loïc; Renard, Catherine M.G.C.
Abstract: The relationship between fruit and puree's characteristics is still poorly understood. In particular, it is not understood how pectin solubilisation and degradation alter the texture of plant-cell dispersions and how a targeted application of processing conditions can be used to design naturally textured food products. Systematic combinations of thermal and mechanical treatments with three different temperatures (70, 83, 95 °C) and grinding speeds (300, 1000, 3000 rpm), applied on one-month (T1) and six-months stored (T6) apples, were used to generate apple purees with contrasted structural and textural characteristics. For T1, serum viscosity increased with increasing temperature (8–104 mPa.s) with a marked increase in pectin solubilisation (1–6 mg/g serum). Pectin macromolecular size and (arabinose + galactose)/rhamnose ratio, estimating pectin side chain branching, decreased with temperature. For T6, pectin showed decreased galactose, leading to facilitated cell separation, low serum viscosity (~16 mPa.s) and restricted impact of process conditions on pectin composition and structure. Grinding had limited impact on pectin solubilisation for T1 and T6 but strongly impacted particle size (498–1096 μm for T1 or 320–1068 μm for T6) and puree's viscosity (871–1475 mPa.s for T1 or 853–1453 mPa.s for T6). Tissue fragmentation was favoured by temperature increase for T1 and by the maturation of raw apples. Process parameters induced differences in the puree's structure and texture depending on the maturation level of raw apples. The observed changes were linked to pectin degradation and substantial side chain loss. Graphical abstract: Image 1 Highlights: Elevated temperature and apple maturation induced pectin degradation. Pectin degradation and solubilisation enhanced cell separation during processing. The interaction storage duration × temperature had a major impact on pectins. Mechanical processes altered pectin composition and structure only slightly. Mechanical treatments highly affected puree's texture but not serum viscosity.